Organocatalytic Coupling of CO2 with Oxetane. Issue 6 (15th November 2016) - Alves, Margot; Grignard, Bruno; Boyaval, Amélie; Méreau, Raphael; De Winter, Julien; Gerbaux, Pascal; Detrembleur, Christophe; Tassaing, Thierry; Jérôme, Christine
Abstract: The organocatalytic coupling of CO2 with oxetanes is investigated under solvent‐free conditions. The influence of the main reaction parameters (type of organocatalytic system, pressure, and temperature) on the yield, the product formed, and the selectivity of the reaction are discussed. An onium salt combined with a fluorinated alcohol promotes the efficient and selective organocatalytic synthesis of α, ω‐hydroxyl oligocarbonates by coupling CO2 with oxetanes at 130 °C and at a CO2 pressure as low as 2 MPa. NMR characterizations were correlated with matrix‐assisted laser desorption/ionization with time‐of‐flight mass spectrometer (MALDI‐TOF) analyses for elucidating the structure of the oligomers. Online FTIR studies under pressure, NMR titrations, and DFT calculations allowed an in‐depth understanding of the reaction mechanism. Finally, CO2 ‐based poly(carbonate‐ co ‐urethane)s were synthesized by step‐growth polymerization of hydroxyl telechelic oligocarbonates with 4, 4′‐methylene diphenyl diisocyanate (MDI). The organocatalytic system described herein constitutes an innovative sustainable route to the selective preparation of hydroxyl telechelic carbonates of high interest for many applications, notably for the polyurethane business (especially for coatings or foams). Abstract : Organically coupled : The use of metal‐free organocatalysts and hydrogen bond donor (HBD) co‐catalysts is reported herein to achieve oxetane/CO2 coupling and synthesize hydroxyl telechelic carbonates with high selectivity. CO2 ‐based polyurethanes for industrial applications can then be synthesized using these oligocarbonates and 4, 4′‐methylene diphenyl diisocyanate (MDI).